If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -7 = 5 + x Reorder the terms: -7 + 2x = 5 + x Solving -7 + 2x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -7 + 2x + -1x = 5 + x + -1x Combine like terms: 2x + -1x = 1x -7 + 1x = 5 + x + -1x Combine like terms: x + -1x = 0 -7 + 1x = 5 + 0 -7 + 1x = 5 Add '7' to each side of the equation. -7 + 7 + 1x = 5 + 7 Combine like terms: -7 + 7 = 0 0 + 1x = 5 + 7 1x = 5 + 7 Combine like terms: 5 + 7 = 12 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| 11(a+b)= | | v=lwh*w | | -6y+10+4y=32 | | 5x+7=8x-(x+1) | | -4n=2 | | 5x+2(11-4x)=84+x | | 18a+4=-8 | | 6x^2-7xy-5y^2=0 | | d=49t | | 3B+1.75=9.25 | | t-3/7=4/7 | | 2k+2k=-10 | | 2(1+3v)+3(v-2)=-49 | | 15x-10=-x+2 | | -8*8-10y=80 | | y+y+x=36 | | 11+ab= | | 24=(-2)(b-3)+8 | | -8*10-10y=80 | | -t+5=y-19 | | 0.52+0.34t=3.59t-1.43 | | 4(z-2)+z=(-13) | | -4(3+5n)-6(-4n+4)=-12 | | f(x+5)=x^2+10x+25+7x+35+7 | | 0.9y-0.5y=4.4 | | -8x-10y=80 | | X+5=-7 | | 24.5+(-45.5)= | | 1/4[4-4x]=10+2(-4) | | 2y+x=36 | | 4x-10+20=90 | | 3x-12-4x+12=x+3-(x-6) |